Histologic and histomorphometric evaluation of new zirconia-based ceramic dental implants: A preclinical study in dogs. Issue 9 (September 2021) - Chacun, Doriane; Lafon, Arnaud; Courtois, Nicolas; Reveron, Helen; Chevalier, Jérôme; Margossian, Patrice; Alves, Antoine; Gritsch, Kerstin; Grosgogeat, Brigitte
Highlights: Ceramic implants as an alternative to Titanium for aesthetic and metal-free solutions. Ce-TZP is more reliable, LTD resistant and tougher than 3Y-TZP. Triphasic Ce-TZP shows similar biocompatibility and osseointegration than Titanium. Abstract: Objective: Healing of soft tissues and improvement of aesthetics have become major research objectives in implantology and renewed the interest for ceramics implants. The aim of this study was to evaluate the pre-clinical performance of screw-shaped sandblasted-etched implants processed from an innovative zirconia-based ceramic composite, in comparison to titanium. Methods: Twenty-four ceramic and twenty-four titanium screw-shaped sandblasted-etched dental implants were tested in a split-mouth design in six Beagle dogs. Surface topographies were investigated by confocal microscopy. Local tissue effects were evaluated at 4 and 13 weeks after implantation through histology. An ANOVA statistical analysis (5% risk; p < 0.05) was performed to compare peri-implant quantitative histomorphometric parameters on buccal and lingual sides, including Bone to Implant Contact (BIC) among test groups and time-periods. Results: Titanium and ceramic implants presented respectively moderate and minimal roughness. After 4 and 13 weeks, ceramic implants showed an inflammatory tissue response close to titanium implants. At both period of time there was no significant difference between the titanium and ceramic groups in terms of BIC values (mean ± SD) at the lingual or buccal sides or when combining buccal + lingual BIC values (respectively for titanium and ceramic, 68.4 ± 14.7 % and 75.0 ± 13.5 % at 4 weeks, and 92.0 ± 8.6 % and 86.1 ± 13.8 % at 13 weeks). Significance: Within the limits of the present study, it can be concluded that newly developed zirconia-based ceramic composite dental implants have similar biocompatibility and osseointegration to those observed in titanium implants. These pre-clinical results corroborate the potential for the use of these new zirconia-based ceramics in oral implantology.